My family matters: Past and future life stories in adolescents with refugee background. Issue 6 (25th June 2019) - Ramsgaard, Stine Breum; Bohn, Annette
Summary: Throughout adolescence, the ability to remember one's personal past and imagine one's personal future in the form of a coherent life story develops. This study explored adolescents' life stories in a group of adolescents with refugee background compared with community controls. In the refugee group, one or both parents had post‐traumatic stress disorder. Adolescents aged 10 to 18 years narrated their past and future life stories and generated cultural life scripts. Contrary to expectations, refugee youth narrated past life stories that were as coherent and positive as community controls'. Interestingly, the refugee group imagined positive future life stories that were more coherent than the control group's. The refugee group mentioned important life themes of family of origin, own feelings, achievements, and helping others. These themes were evident in both the cultural life script and the personal life stories, which might have contributed to more positive and coherent life stories in the refugee group.